Single Mother Parenting Patterns: A Perspective of Islamic Values and its Impact on Education - Daulay, Maslina; Firman, Firman; Neviyarni, Neviyarni (Studi Multidisipliner: Jurnal Kajian Keislaman, 2025)
AbstrakThe phenomenon of single mothers is increasing and poses its own challenges in the child-rearing process, especially in character formation and academic achievement. This condition is an important issue considering the dual role that must be carried out by single mothers, both as breadwinners and as main educators in the family environment. This study aims to examine the parenting patterns of single mothers from the perspective of Islamic values and analyze their impact on children's education in schools. The method used in this study is library research, by examining various scientific literature, books, journals, and relevant documents that discuss parenting in a single mother family, Islamic values in parenting, and the family's contribution to the success of children's education. The data analysis technique used is thematic analysis, which includes the process of data reduction, categorization, data presentation, and conclusion drawn. The results of the study show that the resilience, discipline, and dedication shown by single mothers in carrying out parenting roles based on Islamic values contribute positively to child development. These findings make an important contribution to the understanding that the application of Islamic values in the parenting pattern of single mothers can be an effective strategy in supporting the success of children's education, while strengthening their character foundation in the midst of the challenges of modern life.